A REVIEW OF POVERTY AND EDUCATION OF ADOLESCENCE IN THE URBAN AREA OF COLOMBO, SRI LANKA - Solangaarachchi T. G. K, Gamage H. G. C. L, Adikari A. A. R. E. L (EPRA International Journal of Multidisciplinary Research (IJMR), 2022)
The main intention of this article is to analyze the Poverty and Education of Adolescence in the Urban Area of of Sri Lanka. This study has used literature review method and relevant literature have been analyzed based on descriptive analysis according to the purposes of the study. The purposive sampling method was used to select relevant literature. This study has been analyzed under some major parts namely Poverty and Education in Sri Lanka. This study shows the complete structure of the Poverty in Sri Lanka and its behavior.